Dietary patterns influencing the human colonic microbiota from infancy to centenarian age: a narrative review - Geniselli da Silva, Vitor; Roy, Nicole Clémence; Smith, Nick William; Wall, Clare; Mullaney, Jane Adair; McNabb, Warren Charles (Frontiers in Nutrition, 2025)
Our dietary choices not only affect our body but also shape the microbial community inhabiting our large intestine. The colonic microbiota strongly influences our physiology, playing a crucial role in both disease prevention and development. Hence, dietary strategies to modulate colonic microbes have gained notable attention. However, most diet-colonic microbiota research has focused on adults, often neglecting other key life stages, such as infancy and older adulthood. In this narrative review, we explore the impact of various dietary patterns on the colonic microbiota from early infancy to centenarian age, aiming to identify age-specific diets promoting health and well-being by nourishing the microbiota. Diversified diets rich in fruits, vegetables, and whole grains, along with daily consumption of fermented foods, and moderate amounts of fish and lean meats (two to four times a week), increase colonic microbial diversity, the abundance of saccharolytic taxa, and the production of beneficial microbial metabolites. Most of the current knowledge of diet-microbiota interactions is limited to studies using fecal samples as a proxy. Future directions in colonic microbiota research include personalized in silico simulations to predict the impact of diets on colonic microbes. Complementary to traditional methodologies, modeling has the potential to reduce the costs of colonic microbiota investigations, accelerate our understanding of diet-microbiota interactions, and contribute to the advancement of personalized nutrition across various life stages.